Beneficial Effect Associated with Use of Watery and Alcoholic Extract of Garlic as a Supplement in Hyperlipidemic Guinea Pigs - Choudhary, Kamla; Choudhary, Raghuveer; Choudhary, Prema Ram; Chawla, VK (Journal of Bangladesh Society of Physiologist, 2011)
Background: Garlic is naturally occurring sulphur containing dietary agent belong to Allium family. Members of this family i.e. Garlic, Onions are found to have beneficial effect on atherosclerosis and ischemic heart diseases in both experimental animals and in human beings. Objective: To compare the potency of garlic as antihyperlipidemic and antiplatelet and antithrombotic between its watery and alcoholic extract for their effects. Methods: 25 guinea pigs were fed cholesterol (0.5g/kg body weight) for an initial period of 4 weeks. Cholesterol was then discontinued and the animals were divided into 3 groups. Group-I (n=7) was fed with stock diet and was taken as control. Group-II (n=9) was given 1ml of watery extract and Group-III (n=9) was fed with 1ml of alcoholic extract of garlic with normal diet daily for 4 weeks. The garlic content of both the extract was 2 gm/ml by wt/vol. Fasting blood samples were collected at the end 4 weeks and finally at the end of the study i.e.8 weeks for estimation of serum cholesterol, serum triglyceride, LDC-C, HDL-C, VLDL-C, atherogenic index and platelet adhesiveness index. Bleeding time and clotting time were also detected in all the 3 groups. Results: In the present study, the watery and alcoholic extract of garlic shows significant hypolipidemic activity as they reduced significantly serum cholesterol, serum triglyceride, LDC-C, VLDL-C and atheriogenic index in hyperlipidemic guinea pigs (p<0.01) compared to control. The significant rise in HDL-C was observed in group II but not in group III animals. On comparison between two extracts, watery extract of garlic was more potent hypolipidemic agent, compared to alcoholic extract. Both extract significantly reduces platelet adhesiveness and bleeding time. But between two extract the watery extract was found more potent anti-thrombotic agent as it showed significant decrease in platelet adhesiveness (P<0.01). BT was significantly increased in group II compared to group I and III. Conclusion: It can be concluded that watery extract of Allium Sativum is more potent hypolipidemic and antiplatelet, and anti-thrombotic agent. Key Words: Allium Sativum; Hyperlipidemia; platelet adhesiveness index; watery and alcoholic extracts. DOI: http://dx.doi.org/10.3329/jbsp.v6i1.8079 J Bangladesh Soc Physiol. 2011 June; 6(1): 22-26